KARAKTERISTIK PASIEN LEUKEMIA MIELOID KRONIK DI RUMAH SAKIT UMUM PUSAT SANGLAH DENPASAR TAHUN 2014-2015 - Juliawan, Dewa Gede Angga; Rena, Renny A; Suega, Ketut (E-Jurnal Medika Udayana; vol 5 no 3(2016):e-jurnal medika udayana, 2016)
CHARACTERISTICS OF CHRONIC MYELOID LEUKEMIA PATIENTS IN SANGLAH HOSPITAL DENPASAR ON 2014-2015 In Sanglah Hospital, there are pretty much incidences of chronic myeloid leukemia. There are some characteristic of the patients that can be observed. The treatments are Tyrosine Kinase Inhibitor and Non Tyrosine Kinase Inhibitor . This study use total sampling method. The samples are all patients that had been diagnosed and still seek a medications on 2014-2015. The information are obtained from their medical record, such as gender, age, CML phase, clinical manifestation, history of blood transfusion, Complete Blood Count, BCR ABL qualitative, and medication history.In this study, 41 cases meet inclusion criteria and included as a samples. There are 27 males (65,9%). The mean of age is 38,22±14,09 years old. There are 38 samples (92,7%) in chronic phase, and 3 samples (7,3%) in acceleration phase. Clinical manifestations that have been showed are fever 24 samples (58,5%), decreased body weight 38 samples (92,7%), anemia 34 samples (82,9%), bleeding 15 samples (36,6%), splenomegaly 37 samples (90,2%), and hepatomegaly 11 samples (26,8%). The mean of leukocyte, hemoglobin, and thrombocyte are232,50 x10 3 /µl, 9,25 g/dl, and 436,41x 10 3 /µl. There are 24 samples (58,5%) get blood transfusion. In this study 35 samples (85,4%) have positive BCR ABL qualitative.The medication history areTKI only :13 samples (31,7%), NON TKI only :6 samples (14,6%), and both 22 samples (53,7%).Males is dominant, decreased body weight is the most common clinical manifestation and  most cases is in chronic phase.
Keywords: Characteristic, CML, BCR ABL, RSUP Sanglah